Pengaruh Metode PQ4R terhadap Kemampuan Berpikir Kritis Siswa Kelas 5 Sekolah Dasar: Jenis penelitian kuantitatif - Nadilah, Safira Dina; Anggra Lita Sandra Dewi; Lita Erdiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this research is to determine the effect of the PQ4R method on the critical thinking skills of fifth-grade students at SDN Kedungpeluk 1. The PQ4R method is used to help students remember what they read. Preview means (Skimming), Question means (asking), 4R means read, reflect, recite, review (reading, reflection, summarizing, and thoroughly reviewing). The research conducted is an experimental study using a pre-test, post-test control group design. The instruments used to collect data are tests and observations. The normality test of the data uses Kolmogorov Smirnov with hypotheses 0.074 > 0.05, 0.200 > 0.05, 0.124 > 0.05, 0.200 > 0.05. Meanwhile, the homogeneity test according to the hypothesis shows 0.012 > 0.05, 0.077 > 0.05, 0.081 > 0.05, 0.011 > 0.05. Hypothesis testing is conducted using the t-test formula for independent samples with a value of 0.000 < 0.05. The results of hypothesis testing show that the learning outcomes of the experimental class students are higher than the learning outcomes of the control class students. This is shown in an average score of 93.81 compared to 88.45 for students who received direct learning. The average observation score reached 19.18. It can be concluded that this research has an impact on the critical thinking skills of fifth-grade students when learning using the PQ4R method.